CONTENTS OF MANGANESE, ZINC, COPPER AND MOLYBDENUM IN THE HAIR OF THE FARM ANIMALS IN THE LOWER DNIESTER VALLEY - Tatyana L. Sheshnitsan; Sergey S. Sheshnitsan; Marina V. Kapitalchuk (Юг России: экология, развитие)
Aim. The aim is to identify the differences in the accumulation of manganese, zinc, copper and molybdenum in the hair of farm animals (cows and goats) and their spatial differentiation in the valley of the Lower Dniester. Methods. Sampling and sample preparation were carried out in accordance with generally accepted methods. The determination of metal content in hair samples was carried out in accredited laboratories using atomic absorption spectrometry (AAS) and Inductively Coupled Plasma Spectroscopy (ICP-S). Results. For the first time, data are presented on the content of biogenic metals (manganese, zinc, copper, molybdenum) in the hair of the tail of black-and-white cows and Russian White and Saanen goats in the valleys of the Lower Dniester. Conclusions. It is shown that the concentration of trace elements in the hair of farm animals reflects the relative homogeneity of the biogeochemical conditions of the Lower Dniester valley. It is established that cows and goats are characterized by a sharply differing elemental status for the studied metals estimated on the basis of an analysis of their concentrations in the hair of the tail. At the same time, the effect of hair color on the content of elements was revealed only for molybdenum in cows, and for goats there were no significant interbreed differences in metal concentrations.